Auditoría de gestión a la cooperativa de ahorro y crédito “Ambato” Ltda. sucursal Latacunga, provincia de Cotopaxi, cantón Latacunga, durante el periodo 01 de enero al 31 de diciembre del 2012 - Álvarez Bonilla, Mónica Patricia (2015)
A management Audit evaluates the activities inside entities or organizations, this evaluation allows to determine if the goals and objectives have been established, whose proportioned information lets to give a report which contains recommendations in order that the company can apply them to improve its management. The development of this project was based on the management Audit to “Ambato" Ltd. Cooperative, whose main objective was to reveal several factors, which require more attention in Administrative Management. The interview with the financial institution directors permitted a management audit development because the lack of organization factors established for the staff did not have training manuals. To collect data the authors applied the descriptive method, which permitted analyze past facts and events that determined deficiencies that occurred in the institution during the survey period. The methodological supports used to perform this Audit research were: data collection about the institution functions and activities; work documents preparation according to the appropriate requirements, management indicators application and data collection analysis which allowed obtaining as final result an Audit Report with conclusions and recommendations that improved the institution work.